Shreemad Bhagavat Geeta From Mathematical Perspectives - Joshi, Siddhi Raj (Pragyaratna प्रज्ञारत्न, 2024)
This article is based on the message of Shreemad Bhagvat Geeta, a significant and popular text within the Hindu epic, Mahabharat. An attempt has been made to convey it's meaning with the help of this article. In fact, this is a try to analyze the scripture from the lens of mathematics so that the mathematics community can be benefited with it. Inside the article, the quantification process of our practical life endeavors and some methods related to mathematics teaching are discussed. No mathematical formula and calculations are included here but formulas for solving practical life problems are mentioned.